A 5-year-old Girl with Asymmetric Giant Toes: A Case of Mixed Pattern Macrodystrophia Lipomatosa - Rashid Shahid; Piyush Kumar; Swetalina Pradhan; Upasna Sinha (Wolters Kluwer Medknow Publications, 2024)
Macrodystrophia lipomatosa (MDL) is a rare congenital nonhereditary anomaly, in which progressive overgrowth of mesenchymal tissue leads to disproportionate enlargement of the digits of the hands and feet. We discuss the case of a 5-year-old girl who presented with progressive disproportionate enlargement of the third and fourth toes of the right foot since birth. A diagnosis of MDL was made on the basis of clinical and radiological findings.